Management of anastomotic biliary stricture after liver transplantation and impact on survival. Issue 8 (August 2021) - Jarlot-Gas, Cécile; Muscari, Fabrice; Mokrane, Fatima-Zohra; Del Bello, Arnaud; Culetto, Adrian; Buscail, Etienne; Péré, Guillaume; Fares, Nadim; Péron, Jean-Marie; Cuellar, Emmanuel; Barange, Karl; Kamar, Nassim; et al.
Abstract: Background: Anastomotic biliary strictures (AS) is the main surgical complication after liver transplantation. The aims of this study are to investigate the risk factors of AS, its management and its impact on overall survival and survival of the graft. Methods: All patients who had received a liver transplantation with duct-to-duct anastomosis at Toulouse University Hospital between 2010 and 2016 were included. Results: Of 225 included patients, 56 (24.9%) presented with AS. The median time to discovery of AS was 83 days and 69.6% of the AS appeared within 6 months. Transplantation in critically ill patients, with a liver score >800 points, was an independent predictive factor of survival ( P  = 0.003). The first-line treatment was endoscopic (87.5%), with a success rate of 79.6% and a median of 4 procedures per patient in 12 months. In cases of failure of endoscopic therapy, percutaneous treatment had a high failure rate (50%). AS had no impact in terms of overall survival or in terms of graft survival. Conclusion: AS do not have any repercussions on patient or graft survival, requiring long endoscopic treatment with multiple procedures. In the event of failure of this first-line endoscopic treatment, it seems preferable to turn directly towards surgical repair.